The Implementation of Mutual Legal Assistance between Indonesia and Switzerland Regarding Asset Recovery - Prawira, Muhammad Yudha; Alamsyah, Fatra (Universitas Muhammadiyah Yogyakarta, 2023)
Mutual Legal Assistance in Criminal Matters (MLA) between Indonesia and Switzerland was ratified by the Indonesian government through the enactment of the Law Number 5 of 2020. It outlines the applicable legal framework for reciprocal legal assistance in criminal matters, including the trace of the proceeds of crimes. It is expected that this MLA may facilitate the process of returning assets from Switzerland to Indonesia. This article aims to discuss the implementation of the MLA between Indonesia and Switzerland in returning assets resulted from corruption which were especially stored in Swiss banks. This normative legal research employs both statutory and comparative approach. Analysis was made based on the study upon relevant legal materials, including national legislation, international regulations, and journal articles. It is found that the contribution of the MLA in regard to returning asset resulted from corruption is still minimum. The implementation of the MLA between Indonesia and Switzerland encountered obstacles and various resistance. More serious efforts are needed in order to achieve the main goal of the establishment of the MLA, namely asset recovery.